2017
DOI: 10.4149/neo_2017_203
|View full text |Cite
|
Sign up to set email alerts
|

Association of EGFR and KRAS mutations with expression of p-AKT, DR5 and DcR1 in non-small cell lung cancer

Abstract: The activation of AKT is one of the causes of resistance to epidermal growth factor receptor (EGFR)- tyrosine kinase inhibitors (TKIs). Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) combines with related receptors to trigger apoptosis or protect the cells against TRAIL apoptosis. This research focused on the association of EGFR and KRAS mutations with expression of AKT, p-AKT, DR5 and DcR1 in non-small cell lung cancer. 82 NSCLC patients were included in the study. xTAG liquichip techonolgy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In this study, we found LPCAT1 was highly expressed in A549 and H460 cells compared with the normal human bronchial epithelial cell line Beas-2B. Moreover, KRAS gene is an important downstream molecule in the EGFR signal transduction pathway [51], and KRAS is involved in proper stimulation of PI3K signaling cascade [52]. Previous studies also found that the expression of AKT and p-AKT was significantly higher in NSCLC tissue with KRAS mutation compared to those with wild-type KRAS [51, 53].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found LPCAT1 was highly expressed in A549 and H460 cells compared with the normal human bronchial epithelial cell line Beas-2B. Moreover, KRAS gene is an important downstream molecule in the EGFR signal transduction pathway [51], and KRAS is involved in proper stimulation of PI3K signaling cascade [52]. Previous studies also found that the expression of AKT and p-AKT was significantly higher in NSCLC tissue with KRAS mutation compared to those with wild-type KRAS [51, 53].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that EGFR mutation can activate the downstream PI3K/AKT/mTOR signaling pathway, and lead to the overexpression of AKT and p-AKT, thereby promoting the development of lung cancer. Previous studies (16,21,22) have found that the expression of p-AKT in NSCLC is closely related to poor differentiation and lymph node metastasis, and it is believed that the activation of AKT plays an important role in the development of lung cancer. Other studies, however, have observed the opposite effect.…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed that the positive staining of AKT and p-AKT was observed predominantly in the cytoplasm and occasionally in the nucleus. AKT is overexpressed in various types of human cancer such as lung cancer, breast cancer, and prostate cancer (12,13,16,17). Previous studies have reported positive rates of AKT between 52.1% and 93.3% (13,18,19) and positive rates of p-AKT between 33.3% and 87.5% (13,(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…PTEN participates in growth inhibition, apoptosis promotion, cell cycle regulation, inhibition of cell adhesion and tumor metastasis by regulating the PIP3 pathway (Nosaka, Yamasaki et al 2017, Wise, Hermida et al 2017). The gene deletion and inactivation of PTEN or the over-expression of PIP3 can convert Akt to p-Akt (Zhao, Deng et al 2017). P-Akt acts on downstream mTOR and other substrates through a phosphorylation cascade to promote tumor proliferation and angiogenesis, as well as accelerate tumor invasion and metastasis (Manning and Toker 2017).…”
Section: Discussionmentioning
confidence: 99%